Establishing the Cultural Equivalence of the Young Children's Participation and Environment Measure (YC-PEM) for Use in Singapore. (1st October 2016) - Lim, Chun Yi; Law, Mary; Khetani, Mary; Pollock, Nancy; Rosenbaum, Peter
ABSTRACT: Aims: Establishing the cultural equivalence of clinical assessments is critical to ensuring culturally competent care. Developed in North America, the Young Children's Participation and Environment Measure (YC-PEM) is a caregiver questionnaire of participation in home, preschool, and community activities and perceptions of environmental impact on participation. The purpose of this study is to establish the cultural equivalence of YC-PEM content for use in Singapore. Methods: We conducted semi-structured interviews with ten early childhood and healthcare providers and cognitive interviews with ten parents in Singapore to examine the relevance of original YC-PEM content (activities, environmental factors, item wording). Interviews were transcribed, summarized, and categorized according to item, semantic, conceptual, and operational dimensions of the Applied Cultural Framework that served as a decision-making guide to keep, modify, or delete the items. Results: Providers and parents agreed on conceptual, item and semantic changes but less on operational changes. Significant changes were made to improve comprehension of the YC-PEM. Conclusions: Despite using the same language, the majority of the YC-PEM items needed modification to be relevant to the Singapore culture. Cultural adaptation of the YC-PEM is important because there are cultural differences in children's participation and their environments, as well as the way people understand words.